Direct reinfusion of pericardial blood complications: A case of acute respiratory distress syndrome and disseminated intravascular coagulation - Takuto Yasuda; Kasumi Satoh; Nobuhisa Hirasawa; Manabu Okuyama; Hajime Nakae (Acute Medicine & Surgery)
Abstract Background Direct reinfusion of pericardial blood during cardiac surgery triggers a systemic inflammatory response. Although various inflammatory mediators have been identified as triggers, the role of damage‐associated molecular patterns (DAMPs) remains poorly understood. Despite guidelines recommending against this practice owing to its harmful effects, it is sometimes used in emergencies. Case Presentation A 72‐year‐old man with atrial fibrillation and cerebral infarction developed cardiac tamponade during catheter ablation. He underwent pericardial drainage and direct blood reinfusion. He was transferred to our ICU, where he developed acute respiratory distress syndrome (ARDS) and disseminated intravascular coagulation (DIC). Despite aggressive management, the patient died 41 days after admission. Conclusion This case highlights severe adverse events following direct reinfusion of pericardial blood. These findings suggest a significant role for DAMPs in mediating these inflammatory responses. Direct reinfusion of pericardial drainage blood should be avoided during emergencies to prevent life‐threatening complications.